Can't just stop : an investigation of compulsions - Begley, Sharon , 1956- (New York : Simon & Schuster, 2017)
"Mild compulsions, such as shopping with military precision or hanging the tea towels just so, are something most of us have witnessed, or even engaged in. But compulsions exist along a broad continuum, and at the extremes there exist life-altering disorders. Sharon Begley's meticulously researched book is the first to examine all of these behaviors together--from obsessive-compulsive disorder (OCD) to hoarding, to compulsive exercise, even compulsions to do good. They may look profoundly different, but these behaviors are all ways of coping with varying degrees of anxiety. With a focus on the personal stories of dozens of interviewees, Begley compassionately explores the role of compulsion in our fast-paced culture and the strange manifestations of this very human behavior throughout history. Can't Just Stop makes compulsion comprehensible and accessible, exploring how we can realistically grapple with it in ourselves and in those we love."
Examines the science behind both mild and extreme compulsive behavior, using case studies to understand its deeper meaning and reveal the truth about human compulsion
What is a compulsion? -- 2. Obsessive-compulsive disorder, or,Is Fred in the refrigerator? -- 3. With treatment, from blood in a snowbank to Hollywood -- 4. In the shadow of OCD: carrying conscientiousness too far -- 5. Video games -- 6. Smartphones and the web -- 7. Compulsions past -- 8. Compulsive hoarding -- 9. Compulsive acquiring or I'll take two -- 10. Compelled to do good -- 11. The compulsive brain
Includes bibliographical references and index
Keywords: Obsessive-compulsive disorder